Developing Learning Materials of Project-Based Learning With Integrated Stem To Improve Creative Thinking Skill - Riyanti, Riyanti; Susilaningsih, Endang; Made Darma Putra, Ngurah (Educational Management, 2021)
Learning materials are needed in the implementation of student learning activities to achieve learning success in accordance with the achievement of competencies. Preliminary studies showed that there was still a lack of learning materials development according to the students’ needs. This study aimed to determine the feasibility of science learning materials based on Project Based Learning with integrated STEM to improve students' creative thinking skills and teacher responses to the use of learning materials. The research method used was research and development (R&D) which included several stages, namely problem identification, data collection, design of science learning material using project-based learning with integrated STEM, design validation, design revision, small-scale trials, and big-scale trials. The results showed that the science learning materials developed were suitable for use, namely 3.87 categorized as a very valid category. Moreover, teacher responses obtained 97.33% (very good). Students have an increase in their creative thinking skills up to 0.37 (moderate). Therefore, the use of learning materials using project-based learning with integrated STEM becomes one of the best solutions to improve students' creative thinking skills.